2010
DOI: 10.5935/1806-6690.20100004
|View full text |Cite
|
Sign up to set email alerts
|

Decomposition and nutrients release from crop residues placed on a Yellow Latosol in the savanna of the Maranhão State

Abstract: Resumo -No sistema plantio direto, o uso de plantas de cobertura é uma alternativa amplamente utilizada para aumentar a sustentabilidade do sistema agrícola. O objetivo deste trabalho foi avaliar a decomposição e liberação de nitrogênio (N), fósforo (P) e potássio (K) totais por resíduos culturais, provenientes do pousio e de culturas de cobertura (milheto e braquiária) solteiras e consorciadas, em Latossolo Amarelo no Cerrado Maranhense. O experimento foi conduzido em área sob plantio direto, após a colheita … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…Thus, virtually all the K contained in the phytomass of the plant mixtures (Table 3) was supplied to the soil after 315 days of evaluation. Leite et al (2010), evaluating K release in cover crops, observed that there were differences between treatments for the remaining values at almost all times of collection, except at the last one (100 days), when the treatments did not differ.…”
Section: Rev Bras Cienc Solo 2019;43:e0170402mentioning
confidence: 97%
See 1 more Smart Citation
“…Thus, virtually all the K contained in the phytomass of the plant mixtures (Table 3) was supplied to the soil after 315 days of evaluation. Leite et al (2010), evaluating K release in cover crops, observed that there were differences between treatments for the remaining values at almost all times of collection, except at the last one (100 days), when the treatments did not differ.…”
Section: Rev Bras Cienc Solo 2019;43:e0170402mentioning
confidence: 97%
“…Studies evaluating phytomass decomposition describe a fast release of K in the initial phase of the process (Aita and Giacomini, 2003;Gama-Rodrigues et al, 2007;Leite, 2010 loss of K could be related to the fact that this element does not integrate into "stable" organic structures (Marschner, 1995;Gama-Rodrigues et al, 2007;Taiz and Zeiger, 2013;Gómez-Muñoz et al, 2014). One of the main mechanisms driving K release is leaching, so mineralization is not a pre-requisite for its transfer to the soil (Gama-Rodrigues et al, 2007).…”
Section: Rev Bras Cienc Solo 2019;43:e0170402mentioning
confidence: 99%
“…Author(s) agree that this article remain permanently open access under the terms of the Creative Commons Attribution License 4.0 International License raising to considerable levels of soil organic matter and nutrients (Leite et al, 2010). The crop rapid development enables the use of sunn hemp in cropping systems with rotation and crop succession.…”
Section: Introductionmentioning
confidence: 95%
“…The sunn hemp (Crotalaria juncea L.) is a cover crop option for soil protection due to its hardiness, high dry matter production and nitrogen fixation (Silva and Menezes, 2007), improving and maintaining soil quality, raising to considerable levels of soil organic matter and nutrients (Leite et al, 2010). The crop rapid development enables the use of sunn hemp in cropping systems with rotation and crop succession.…”
Section: Introductionmentioning
confidence: 99%
“…Among the various botanical families species that can be grown as green manures, stand out those of the Fabaceae family. The legumes in addition to providing similar benefits to other species, have the ability to accumulate N through biological fixation (Melo, 2012;Da Silva et al, 2009;Leite et al, 2010).…”
Section: Introductionmentioning
confidence: 99%